Proses Pengadaan Bahan Pustaka Perpustakaan Sekolah - Zahra, Selia Febi (Nusantara Journal of Information and Library Studies (N-JILS), 2023)
The process of procuring library materials becomes an element of the management process of a library. Procurement of library materials is also a way that can be done by the library in an effort to provide appropriate information needs of users. This process is also usually carried out by the school librarian and is a way for the school librarian to provide information and interests that are appropriate to the school's students. This study aims to examine the process of procuring library materials in the school library and the factors that can hinder the process of procuring the collection. The research method used is a literature study based on other studies that have been done previously. The results of this study found that in the process of procuring collection materials there are four steps, namely carrying out an inventory of library materials that are planned to be owned by the library, analyzing library material needs from library users, determining priorities, determining the methods used in procuring library materials. And the factors that influence the process of procuring library materials can be influenced by internal factors and external factors.